2021
DOI: 10.2147/cmar.s290738
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Platelet-to-Lymphocyte Ratio (PLR) in Extrahepatic Metastasis of Hepatocellular Carcinoma After Curative Resection

Abstract: Background The prognosis for patients diagnosed of hepatocellular carcinoma (HCC) who have extrahepatic metastasis after liver resection is unsatisfactory. This study aimed to find out the relationship between the inflammation-related indexes and metastasis. Methods One thousand three hundred and sixty-six patients diagnosed of HCC who underwent curative resection were included in this study and divided into metastasis group (n=180) and non-metastasis group (n=1186). A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 27 publications
1
5
1
Order By: Relevance
“…However, the prognostic accuracy of the models including the SII and PLR in our cohort was not better compared with the models including NLR and MLR. This is in opposition with the results of other studies on SII and PLR, which showed a prognostic accuracy in cancer patients [42,43], as well as a good predictive role for neurological long-term complications in CO-poisoned patients [23], probably because we were interested only in short-term outcomes and we did not analyze the long-term effect of these indices. Thrombocytopenia might appear after the oxidative stress which negatively affects the platelet membranes, as it does in all blood cells.…”
Section: Discussioncontrasting
confidence: 89%
“…However, the prognostic accuracy of the models including the SII and PLR in our cohort was not better compared with the models including NLR and MLR. This is in opposition with the results of other studies on SII and PLR, which showed a prognostic accuracy in cancer patients [42,43], as well as a good predictive role for neurological long-term complications in CO-poisoned patients [23], probably because we were interested only in short-term outcomes and we did not analyze the long-term effect of these indices. Thrombocytopenia might appear after the oxidative stress which negatively affects the platelet membranes, as it does in all blood cells.…”
Section: Discussioncontrasting
confidence: 89%
“…In addition, PLR is an independent risk factor for the prognosis of coronavirus disease in 2019 [ 18 , 19 ], and a high PLR is significantly associated with mortality. A clinical study [ 20 ] also showed that PLR is an independent risk factor for postoperative metastasis of malignant tumors, and a high PLR indicates a higher rate of postoperative metastasis. Several differential diagnosis studies [ 14 , 21 ] have shown that PLR is an important index for establishing a predictive model for the diagnosis of leiomyoma.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies [34][35][36] have pointed out that inflammation plays an important role in the pathogenesis of uterine leiomyoma, as well as in the development of fibroid fibrosis and disease progression. Many studies [20,23,37,38] have also reported that PLR and NLR can reflect the inflammatory state of the body in the absence of infectious diseases. In the current study, NLR showed an upward trend with an increase in PLR in patients with multiple uterine fibroids.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have proposed markers based on several nutritional or inflammation‐based prognostic indicators of HCC. Nutritional‐ or inflammation‐based markers include the prognostic nutritional index, 32 , 33 , 34 controlling nutritional status (CONUT) score, 35 , 36 , 37 Glasgow prognostic score, 38 C‐reactive protein (CRP)‐to‐albumin ratio (CAR), 39 neutrophil‐to‐lymphocyte ratio (NLR), 40 platelet‐to‐lymphocyte ratio (PLR), 41 , 42 lymphocyte‐to‐monocyte ratio (LMR), 43 , 44 and CRP‐albumin‐lymphocyte index. 45 Table 1 shows combined indices that can reportedly be used to estimate the nutritional or inflammatory status relevant to short‐ and long‐term outcomes after hepatectomy for HCC.…”
Section: Nutritional Status Of Patients With Liver Cancermentioning
confidence: 99%